Functional exercise capacity and health-related quality of life in people with asbestos related pleural disease: an observational study - Dale, Marita T (BioMed Central, 2013)
BACKGROUND: Functional exercise capacity in people with asbestos related pleural disease (ARPD) is unknown and there are no data on health-related quality of life (HRQoL). The primary aims were to determine whether functional exercise capacity and HRQoL were reduced in people with ARPD. The secondary aim was to determine whether functional exercise capacity was related to peak exercise capacity, HRQoL, physical activity or respiratory function. METHODS: In participants with ARPD, exercise capacity was measured by the six-minute walk test (6MWT) and incremental cycle test (ICT); HRQoL by the St George’s Respiratory Questionnaire and physical activity by an activity monitor worn for one week. Participants also underwent lung function testing. RESULTS: 25 males completed the study with a mean (SD) age of 71 (6) years, FVC 82 (19)% predicted, FEV(1)/FVC 66 (11)%, TLC 80 (19)% predicted and D(L)CO 59 (13)% predicted. Participants had reduced exercise capacity demonstrated by six-minute walk distance (6MWD) of 76 (11)% predicted and peak work rate of 71 (21)% predicted. HRQoL was also reduced. The 6MWD correlated with peak work rate (r=0.58, p=0.002), St George’s Respiratory Questionnaire Total score (r=-0.57, p=0.003), metabolic equivalents from the activity monitor (r=0.45, p<0.05), and FVC % predicted (r=0.52, p<0.01). CONCLUSIONS: People with ARPD have reduced exercise capacity and HRQoL. The 6MWT may be a useful surrogate measure of peak exercise capacity and physical activity levels in the absence of cardiopulmonary exercise testing and activity monitors. TRIAL REGISTRATION: ANZCTR12608000147381